Retrograde Intrarenal Surgery Versus Shock Wave Lithotripsy for Renal Stones Smaller Than 2 cm: A Randomized Clinical Trial - Javanmard, Babak; Kashi, Amir Hossein; Mazloomfard, Mohammad Mohsen; Ansari Jafari, Anahita; Arefanian, Saeed (Urology Journal, 2016)
Purpose: To compare outcomes of retrograde intrarenal surgery (RIRS) with extracorporeal shock wave lithotripsy (SWL) for stones ≤ 2 cm. Materials and Methods: Patients who were diagnosed with kidney stones of ≤ 2 cm underwent RIRS or SWL in a parallel group randomized clinical trial with balanced randomization [1:1] from 2011 to 2014. The primary outcome of interest was stone free rate after a single session intervention. Patients were evaluated by ultrasonography and KUB at 1 and 3 months after the intervention for the presence of residual stone by a radiologist who was blinded to the study. Results: The stone free rate one month after a single session intervention in the RIRS group was higher than the SWL group (90% versus 75%, P = .03). The success rates after two sessions of RIRS versus SWL were 96.7% versus 88.3% respectively. (P = .08) Patients in the RIRS group had significantly lower postoperative visual analogue pain score compared to the SWL group (5.2 ± 2.8 versus 3.1 ± 2.7, P < .001). Steinstrasse formation and renal hematoma were observed in 4 and one patient in the SWL group versus no patient in the RIRS group. Postoperative hospital stay was significantly shorter in the SWL group (6.7 ± 1.3 versus18.9 ± 4.3 hours, P < .001). Conclusion: The RIRS procedure is a safe treatment option for renal stones of ≤2cm with less pain and higher success rate at first session compared to SWL.